First: factor the equation:
(x + 1)(x + 6) = 0
Second: take both sets and equal them to "0" > solve for "x" >
x + 1 = 0
x + 1 - 1 = 0 - 1
x = -1
x + 6 = 0
x + 6 - 6 = 0 - 6
x = -6
2006-12-29 16:45:14
·
answer #1
·
answered by ♪♥Annie♥♪ 6
·
1⤊
0⤋
x2+7x+6= 0 for x
(0)2 + 7(0) +6=
0+0+6=
0+6 x=6 casey a 9 grade
2006-12-29 14:57:33
·
answer #2
·
answered by casey v 1
·
0⤊
3⤋
Assuming you mean X^2 + 7x + 6 = 0 then....
(x + 1)(x + 6) = 0
x = -1 or x = -6
2006-12-29 14:53:07
·
answer #3
·
answered by tkquestion 7
·
1⤊
0⤋
If x is 0, find all the solutions including x.
So, 7x= 0
x2=0
Plug these things in-
0+0+6
Simple, the answer to this question is 6.
2007-01-02 10:30:28
·
answer #4
·
answered by Anonymous
·
0⤊
0⤋
x^2 + 7x +6 = 0
x^2 +6x +x + 6 = 0
x(x+6) +1(x+6) =0
(x+6) (x+1) = 0
x+6 = 0 x+1=0
x=-6 x=-1
Answer: x= -6 and -1
2006-12-29 14:56:05
·
answer #5
·
answered by ? 3
·
1⤊
0⤋
x² + 7x + 6 = 0
(x + 6) (x + 1)
- - - - - -
Roots
x + 6 = 0
x + 6 - 6 = 0 - 6
x = - 6
- - - - - -
x + 1 = 0
x + 1 - 1 = 0 - 1
x = - 1
- - - - - - - -
X = - 6
or
x = - 1
- - - - - - - - -s-
2006-12-30 01:44:24
·
answer #6
·
answered by SAMUEL D 7
·
0⤊
0⤋
x² + 7x + 6 = 0
(x+1)(x+6) = 0
D = 7² - 4.1.6
D = 49 - 24
D = 25
x = (-7 +/- 5) : 2
x' = (-7 + 5) : 2 = -1
x" = (-7 - 5) : 2 = -6
Thus,
{x elements of R | x' = -1 or x" = -6}
>`´<
2006-12-29 17:01:28
·
answer #7
·
answered by aeiou 7
·
0⤊
0⤋
(x+6)(x+1)=0
x+6=0 or x=-6
x+1=0 or x=-1
2006-12-29 15:23:23
·
answer #8
·
answered by raj 7
·
1⤊
0⤋
* 2x + 7x + 6 = 0 (u'll transpose variables to the right)
* 2x + 7x = -6 + 0 (and non variable to the right)
* 9x = -6 (if u transpose any num. change the sign)
(divide both by nine)
x = -2/3
2006-12-29 15:21:55
·
answer #9
·
answered by rosaine_78 1
·
0⤊
3⤋
There are several ways to solve this,
quadratic formula, factoring, etc.
I suggest factoring.
(x+1)(x+6) jumps out right away
that means x=-1, and x=-6
2006-12-29 14:53:11
·
answer #10
·
answered by enginerd 6
·
1⤊
0⤋